2022
DOI: 10.1007/s12111-022-09591-5
|View full text |Cite
|
Sign up to set email alerts
|

Black People Narrate Inequalities in Healthcare Systems that Hinder COVID-19 Vaccination: Evidence from the USA and the UK

Abstract: The coronavirus disease 2019 (COVID-19) pandemic is an unprecedented global health emergency. As a novel condition, there is no known definitive treatment for the condition, except for the use of vaccines as a control measure. In the literature, the issue of inequalities in healthcare systems has been documented as a hindrance to COVID-19 vaccination; however, the specific inequalities in healthcare systems that hinder COVID-19 vaccination are poorly understood. Guided by the fundamental cause theory (FCT), th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 39 publications
0
4
0
Order By: Relevance
“…It may also aid public health practitioners in bringing attention to the important role that structural racism plays in creating and maintaining racial health disparities. Ogueji et al recently reported that U.S. adults have little appreciation for the influence of structural racism on COVID-19 vaccination rates [ 33 ]. Providing people with actual numbers to document the magnitude of racial health disparities and the magnitude of structural racism may help the public and policy makers to acknowledge [ 33 ] structural racism as a fundamental cause of adverse health.…”
Section: Discussionmentioning
confidence: 99%
“…It may also aid public health practitioners in bringing attention to the important role that structural racism plays in creating and maintaining racial health disparities. Ogueji et al recently reported that U.S. adults have little appreciation for the influence of structural racism on COVID-19 vaccination rates [ 33 ]. Providing people with actual numbers to document the magnitude of racial health disparities and the magnitude of structural racism may help the public and policy makers to acknowledge [ 33 ] structural racism as a fundamental cause of adverse health.…”
Section: Discussionmentioning
confidence: 99%
“…In this sense, some studies have analyzed vulnerable minority groups. Thus, Ogueji et al [ 37 ] examined a narrow sample of 35 Black people, aged between 21 and 58, from the USA and the UK, to see to what extent they felt the injustices in the health system, reflected in the absorption of COVID-19 vaccines; it turned out that more participants from the UK reported blockages related to historical factors, residence, uniform application of health policies or differentiated actions, compared to those from the USA [ 37 ]. Other researches identified racial disparities in relation to the acceptability of the COVID-19 vaccine.…”
Section: Literature Reviewmentioning
confidence: 99%
“…It is well reported that inequalities will arise because of the barriers people and communities face when accessing health and care services, which then leads to mistrust of these systems. 29 This can then lead to inequalities in terms of access to information and the creation of the types of services which best suit particular communities. 30…”
Section: Inequalities and Trust In Vaccinesmentioning
confidence: 99%